2023
DOI: 10.3390/en16104224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Heat Transfer in Electronic Radiator Filled with Metal Foam

Abstract: The performance of an electronic radiator filled with metal foam with a porosity of 96% was studied. The effect of the factors including the flow rates, the pores per linear inch (PPI) and the numbers of fins was analyzed. The results show that the electronic radiator with metal foam reflects a stronger ability of the heat transfer compared to the electronic radiator without metal foam. With the increase in the flow rate between 10 L/h and 60 L/h, the heat transfer coefficient of both of the two electronic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Metal foams can reduce the size and mass of devices because of their low density. Shan et al [23] studied heat transfer in an electronic radiator filled with metal foam. The authors analysed the effect of several factors, such as flow rate, pores per linear inch, and number of fins, on the heat transfer coefficient.…”
Section: Review Of New Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal foams can reduce the size and mass of devices because of their low density. Shan et al [23] studied heat transfer in an electronic radiator filled with metal foam. The authors analysed the effect of several factors, such as flow rate, pores per linear inch, and number of fins, on the heat transfer coefficient.…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…The authors proved that the metal foam reflects a much stronger ability of heat transfer compared to the electronic radiator without the metal foam. They found the optimal number of fins and observed that the higher the number of pores per linear inch, the greater the heat transfer coefficient [23].…”
Section: Review Of New Advancesmentioning
confidence: 99%